The Formulation of Rambutan Leaf (Nephelium lappaceum L.) Extract on Syrup Preparation - Derry eviana Pratiwi (Universitas Muhammadiyah Surakarta, 2020)
Diabetes mellitus is a group of metabolic disorders characterized by hyperglycemia due to the abnormal metabolism of carbohydrates, fats, and proteins. Flavonoids are compounds that can reduce glucose levels in the blood. Rambutan leaves (Nephelium lappaceum L) are one of the plants that contain flavonoids. This research is an experimental study at producing concentrations of syrup for diabetes treatment with various propylene glycol as cosolvent. Rambutan leaves were extracted using the maceration method with 96% ethanol. Rambutan leaf extract made syrup preparations using propylene glycol with concentrations of 0%, 11%, 12%, and 13%. Syrup obtained by testing included: organoleptic, homogeneity, BJ, pH, viscosity, displaced volume, and acceptability. Based on the research on rambutan leaf extract formulation on syrup preparations showed that the addition of propylene glycol has an effect on taste which is giving a sweet taste so that the addition of propylene glycol can improve the taste in the preparation of rambutan leaf extract syrup. The concentration of propylene glycol 11% produced a preparation of rambutan leaf extract with the best physical stability.